Problems of Implementation of the Constitutional Complaint in Ukraine and Ways to Resolve them - SHCHERBANYUK, Oksana (Journal of Advanced Research in Law and Economics; Vol 11 No 2 (2020): JARLE Volume XI Issue 2(48) Spring 2020, 2020)
The article explores the problems of implementation of the constitutional complaint in Ukraine and proposes ways of its solving. In terms of integration of Ukraine to the European Union there is a harmonization of the Ukrainian legislation to the European standards, so the analysis of foreign experience of functioning of institute of constitutional complaint is necessary to solve the problems in this area. Therefore, the main method in methodology of research of problems of implementation of constitutional complaints is comparative legal. As from 2016, Ukraine has introduced a normative model of individual constitutional complaint, which allowed physical persons and legal entities of private law to apply to the Constitutional Court of Ukraine for protection of violated constitutional rights, freedoms and legitimate interests. The article analyzes the jurisprudence of the Constitutional Court of Ukraine clarifies the admissibility criteria of the constitutional complaint in Ukraine, the procedural filters and proposed solutions of problems to improve the protection of rights and lawful interests of persons. It is concluded that the mechanism of the submission and consideration of the constitutional complaint, the algorithm of selection (filtering) of the constitutional complaints needs significant improvement with consideration for the European experience. In our opinion, the legal effect of the constitutional-legal institution will be made only in connection with the introduction of a complete, not normative constitutional complaint, which will significantly increase the responsibility of subjects of law-making, law enforcement, protection of human rights and ensure the authority of the Constitution of Ukraine.